2015
DOI: 10.1111/ijjs.12034
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Capital on Men's Mental Health from the Perspective of Social Support Theory

Abstract: This study examines the effects of social capital as it affects men's mental health in the context of work–family balance. Multivariate analyses of data from National Family Research of Japan 2008 have revealed the following. First, the social capital that men receive from their spouses was found to have a direct effect on their distress. The effect of social capital from family other than a spouse does not have a direct effect on men's mental health. Second, only social capital from a spouse was observed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Individuals with more resources can better deal with conflicts between the work domain and the family domain, thus decreasing the degree of conflict between work and family. Previous studies have widely adopted a social support theory perspective to explore the outcomes of social support behavior, 41,42 In this article, through the COR theory, the 2-way mediating role of work-family conflict is explained as an internalization process of resource transfer. The resources of individuals are limited, mutual occupation, and consumption of resources exist in the work domain and the family domain.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with more resources can better deal with conflicts between the work domain and the family domain, thus decreasing the degree of conflict between work and family. Previous studies have widely adopted a social support theory perspective to explore the outcomes of social support behavior, 41,42 In this article, through the COR theory, the 2-way mediating role of work-family conflict is explained as an internalization process of resource transfer. The resources of individuals are limited, mutual occupation, and consumption of resources exist in the work domain and the family domain.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell and Lagory (2010) found that while bridging social capital displays a small inverse relationship with distress, bonding social capital appears to increase an individual's level of mental distress in an impoverished community. Bae (2015) pointed out that the social capital obtained from non-spouse family members does not positively, even might negatively, influence health status.…”
Section: Literature Reviewmentioning
confidence: 99%